2019
DOI: 10.2172/1570349
|View full text |Cite
|
Sign up to set email alerts
|

Consequence Analysis of Residual Water in a Storage Canister (Preliminary Report)

Abstract: This report describes an investigation of materials' interactions due to residual water remaining inside a dry storage canister, and the impacts on the spent nuclear fuel and canister internals.Recent findings from the High Burnup Demonstration project, and an Integrated Research Project, sponsored under the DOE-Nuclear Energy, Spent Fuel and Waste Disposition campaign, show that residual free water, well above the amount of approximately 0.4 gm-moles that had been assumed for a 3 torr rebound pressure, may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Define the volume increase as Δ = − 0 , then Note that, if the pellet has no void space ( = 0) and if UO2 is fully oxidized to U3O8 ( = 1), then Δ = − 1 = 0.36443 which is the conversion limit or the maximum net volume expansion of the pellet (36% by volume) [30][31][32].…”
Section: Calculation Of Total Volume and Volume Changementioning
confidence: 99%
“…Define the volume increase as Δ = − 0 , then Note that, if the pellet has no void space ( = 0) and if UO2 is fully oxidized to U3O8 ( = 1), then Δ = − 1 = 0.36443 which is the conversion limit or the maximum net volume expansion of the pellet (36% by volume) [30][31][32].…”
Section: Calculation Of Total Volume and Volume Changementioning
confidence: 99%
“…Residual water (post-drying and sealing) in a spent nuclear fuel (SNF) canister can result in corrosion and radiolysis that could affect the spent nuclear fuel and canister internal structural materials [CNWRA 2013, Shukla et al, 2019. Recent work [Bryan et al, 2019a] showed that inadvertent free water (~100 ml) may remain following drying even with a dryness criterion of 3 torr pressure limit following a 30-minute hold after active drying is complete a and measured ~500 ppmv of H2 after 12 days post-dryout in the High Burnup (HBU) Demonstration Cask.…”
Section: Introductionmentioning
confidence: 99%
“…The study considered residual water amount as high as 55 moles (CNWRA, 2013). A report under the SFWST program prepared in 2019 updated and refined the corrosion/oxidation models used in the NRC work (Shukla, et al, 2019). Both of those studies did not explicitly look at the corrosion of non-fuel canister internals.…”
Section: Introductionmentioning
confidence: 99%